Taysir dalam ibadat haji dan umrah: Kajian berdasarkan keputusan muzakarah haji kebangsaan / Ahmad Salahuddin Harun - Ahmad Salahuddin , Harun (2018)
Hajj is the fifth pillar of Islam which is obligatory and entrusted by Allah S.W.T through His Prophet S.A.W. Therefore, Muslims should comply with the right action in performing Hajj by His Prophet S.A.W. However, technological advancement lead to increasing number of pilgrims and caused congestion in Mash‟ar al-Haram. For instance, tragedy in 1990, recorded a large number of pilgrim‟s death which led to implementation of taysir concept although the practice is not similar to during Prophet Muhammad S.A.W era. Hence, the concept of taysir is needed to solve problems arose from the changes. The objectives of this study are twofolds. The first is to examine the meaning of taysir and it‟s dawabit. The second is to identify the issues decided by National Hajj Muzakarah and analyse the issues decided. This study employed various type of data collections. The first is by utilising the data set from Muzakarah Hajj decision reports and the second is by using primary data collection which is to interview experts in the field of pilgrimage. Besides that, this study also conducted field research in Mecca during Hajj season (1436 H and 1437 H) to observe problems and deduce suitable solutions. One of the main issues identified is the issue of menstrual, where, for females who need to leave Mecca but yet to complete tawaf ifadah can perform their tawaf without the need to wait for 24 hours. . Next is the issues of „waktu melontar‟ during tasyriq. It is believed that restricted „Waktu Melontar‟ for certain group of pilgrims after sunrise has been overcome by extension of Jamrah. Looking from the perception of tawaf wada‟, the distance between Jeddah and Mecca is less than 2 marhalah. In that case, Muslims who went for a visit at Jeddah is not required Tawaf Wada‟. Thus, this study concluded taysir concept exercised by National Hajj Muzakarah, but it must be ascertained that the taysir practiced coincided with the accuracy of the syara ' and is not merely because of the convenience.